KAJIAN POTENSI UMBI ANUWUN (Tacca leontopetaloides l. Kuntz ) SEBAGAI SUMBER PANGAN ALTERNATIF - Kogoya M; D. Rawung; M.F. Sumual; G.S.S. Djarkasi (Universitas Sam Ratulangi, 2017)
ABSTRACTThe objectives of this research were to find out nutrition composition and the unwanted components such as oxalates and HCN of tacca (Tacca leontopetaloides L. Kuntz) tubers from Talaud district and to developed products using its starch. The results showed the starch was tubers’ main nutrition components which accounted for 24.32% wet basis and 71.85% water content. The HCN and oxalates contents, however, were also high (3 and 40mg/100g, respectively). Tacca tuber could be processed into starch flour (85,74% starch), wheres other components such as ash, protein, fat and crude fiber were under 1.0%. Processing of starch resulted in cookies with high acceptable score. It was concluded that tacca tubers could be used as alternative carbohydrate food source and can be processed into various products. It is neccesary, however, to consume with other high fat, protein and vitamin foods to compolement the nutritoon of tacca.Keywords: tacca anuwun, starch